Abusive Supervision, Leader-Member Exchange, and Creativity: A Multilevel Examination - He, Changqing; Teng, Rongrong; Zhou, Liying; Wang, Valerie Lynette; Yuan, Jing (Frontiers in Psychology, 2021)
Despite the growing research attention on the topic of abusive supervision, how abusive supervision affects individual and team creativity have not yet been thoroughly investigated. Drawn from the perspective of leader-member exchange (LMX), the current study develops a multilevel model to explore the relationships between abusive supervision and creativity at both team and individual levels, with a focus on the roles played by team-level leader-member exchange (TLMX) and LMX differentiation (DLMX). Based on multi-source data collected from 325 team members and their team leaders in 72 teams, the results show that abusive supervision has a negative relationship with TLMX, a practice that is conducive to both team and individual creativity. At the team-level, the negative relationship between abusive supervision and TLMX is lessened by a higher level of DLMX. In addition, the positive relationship between TLMX and team creativity is weakened by a higher level of DLMX. The theoretical and practical implications of these findings are discussed.